2019
DOI: 10.3390/ijerph16132296
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Predicting Dengue Incidence in Highly Vulnerable Countries using Panel Data Approach

Abstract: The spread of dengue has become a major public health concern in recent times due to alarming climate change. Using country level panel data over the 2000–2017 period, this paper examines the effects of climate change and socio-economic variables on the incidence of dengue-borne diseases in some of the most highly vulnerable countries. Empirical analysis shows a positive association between climate change and socio-economic conditions in the advent of dengue-borne diseases. We find that climate change, as meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
1
9
1
Order By: Relevance
“…The coefficient values of income, education, and population density are −0.6951 ( p -value < 0.01), −0.0160 ( p -value > 0.05), and 0.1093 ( p -value > 0.05), respectively, revealing that a 10-unit increase in income results in a 0.6951% decrease in neonatal deaths because of acute respiratory infection in selected Asian countries. These results are in line with the previous studies available in literature [12,35,36,37,38].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The coefficient values of income, education, and population density are −0.6951 ( p -value < 0.01), −0.0160 ( p -value > 0.05), and 0.1093 ( p -value > 0.05), respectively, revealing that a 10-unit increase in income results in a 0.6951% decrease in neonatal deaths because of acute respiratory infection in selected Asian countries. These results are in line with the previous studies available in literature [12,35,36,37,38].…”
Section: Resultssupporting
confidence: 93%
“…The authors further validated income and education level negatively affecting the neonates’ deaths. An increased income enhances an individual’s demands with reference to quantity, quality of goods and services, and utilization of public and private health facilities for themselves and their siblings, which improves overall health status [37,38]. An increased income has positive association with the government’s provision of better resources for public health services, thus reducing mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also supports other findings in Central Visayas in Philippines (Picardal and Elnar, 2012), which found uncorrelated of temperature and rainfall variability on the dengue prevalence. However, this is contrary to many studies reported previously that temperature was significantly association with dengue cases (Sang et al, 2014, Wangdi et al, 2018, Anwar et al, 2019, rainfall was significantly association with dengue cases (Méndez-Lázaro et al, 2014, Dhewantara et al, 2019. Temperature, rainfall, and mean relative humidity demonstrated predictive potential in some countries, but not all.…”
Section: Resultscontrasting
confidence: 98%
“…This is evident from adding average education as a control variable, as shown in Table 3 . Education does not only help in increasing economic growth and individual’s incomes, but it also helps in developing behaviors and habits that contribute positively to an individuals’ health [ 36 ]. Educated parents have a greater ability to provide better care to their children, and make the best use of the health and other social services accessible to them.…”
Section: Discussionmentioning
confidence: 99%